Identification of a novel undecamethylhenicosane and three oxygenated precursors in a Maoming Basin shale, China. (March 2020) - Liao, Jing; Lu, Hong; Feng, Qiao; Zhou, Youping; Shi, Quan; Peng, Ping'an; Sheng, Guoying
Highlights: A new C32 botryococcane was identified by NMR. A new C32 botryococcane biomarker is proposed for the B race of B. braunii . A C32 botryococcanal and two C31 botryococcanols were also tentatively identified. Bacterial degradation is proposed for the formation of the alkanal and alkanols. Abstract: Further to our recent identification of a C33 botryococcane, a C33 botryococcan-24-one and two C31 botryococcanes (2, 3, 6, 7, 10, 12, 15, 16, 19, 20-decamethylhenicosanes: C31 DMHs) with a methyl group β-positioned to the sole quaternary carbon in the skeleton in a sediment sample from the Maoming Basin, we report the NMR-based structural identification of a new C32 botryococcane (2, 3, 6, 7, 10, 10, 12, 15, 16, 19, 20-undecamethylhenicosane: C32 UMH), and MS-based structural identification of a C32 botryococcanal (C32 UMH-al) and two C31 epimeric botryococcanols (C31 DMH-ols) in the same sediment sample after trimethylsilylation. These three oxygenated botryococcanoids are speculated to possess the same β-positioned methyl group (to the sole quaternary carbon). We propose that the C32 UMH-al and two epimeric C31 DMH-ols are degradation products of the CC double bond in the ethenyl group connected to the sole quaternary carbon in their biological precursor C33 botryococcene with a unique β-positioned methyl group (to the quaternary carbon), and are geochemical precursors for the C32 UMH and previously identified C31 DMHs, respectively. Since it is known that abiotic degradation (photo-mediated or autoxidation) preferentially acts on the internal double bond while sedimentary bacteria preferentially degrade the terminal double bond, our finding of a degraded terminal C24-25 double bond and an intact internal double bond (at C11-12) is indicative of bacterially mediated degradation. A detailed bacterially mediated degradation pathway is proposed to explain the formation of C31 –C33 botryococcanes and their oxygenated derivatives.